PAŃSTWO PRAWA I KOŚCIÓŁ PRAWA - Baldus, Manfred (Wydział Prawa i Administracji UAM, 2010)
Szereg doświadczeń zebranych w okresie panowania narodowosocjalistycznej samowoli oraz we wczesnych latach istnienia Niemieckiej Republiki Demokratycznej spowodowało, ze w dzisiejszych Niemczech poświęca się szczególną uwagę zasadzie państwa prawa. Zarówno demokracja, jak i republikańska forma państwa stanowią w sposób oczywisty podstawę niemieckiej konstytucji. ,,Państwo prawa” w życiu codziennym łączy się przede wszystkim z ochroną państwa. Innymi słowy, jawi się jako ,,państwo drogi prawnej”, jako sędziowska kontrola oparta na zasadach niezależności, sprawiedliwego postępowania, rzetelnego wysłuchiwania uczestników postępowania oraz kontroli instancyjnej. Najpierw zatem przybliżono praktykę państwa prawa, a następnie z tej perspektywy aktualne problemy Kościoła katolickiego.

*Owing to the historical experiences of the Nazi era and the former German Democratic Republic, the constitutional state (Rechtsstaat) is of particular importance to the German public nowadays. In everyday life the constitutional state is seen as a state that guarantees legal protection, judicial control exercised by an independent judge, a fair trial, a court hearing, and a possibility of appeal. In this paper, the author describes a number of current problems with which the constitutional state must cope, such as the tension between legal certainty and justice, or between parliament and jurisdiction. Like any societas constituta et ordinata also the church needs judicial authorities in order to solve its internal conflicts. The author presents the main efforts that have been made to reduce the evident deficits of the legal protection, mainly at the local church level.
A CONSTITUTIONAL STATE AND THE CHURCH UNDER THE RULE OF LAW
Keywords: Państwo prawa; Constitutional state; Kościół prawa; Church under rule of law; Niemcy; Germany